(untitled) - Korngold, Alice (San Francisco, CA, 2005)
Leveraging Good Will shows how nonprofit organizations can access the extraordinary resources of businesses, and how for-profits can benefit from partnering with nonprofits. Written by Alice Korngold—an expert in matching business professionals with nonprofit organizations—this important resource clearly demonstrates how nonprofits can gain valuable experience, expertise, relationships, and funding that will elevate and advance their organizations while businesses can build stronger relationships with the community and develop the next generation of leaders. Filled with illustrative examples and real-life success stories, Leveraging Good Will is an insider’s guide to what it takes for nonprofits to transform their organizations through partnerships with businesses. Step by step, the book outlines how to create a solid plan based on proven-in-practice techniques.
Keywords: Nonprofit organizations,Nonprofit organizations; Management,Finance; United States,United States